LITERATURE REVIEW OF FACTORS AFFECTING TAX AVOIDANCE IN BANKING COMPANIES LISTED ON THE IDX - Wulandari, Putri Ayu; Nilasari, Ayunda Putri (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Various studies have been conducted to look at factors that may or may not influence companies to practice tax avoidance. Several factors are discussed such as profitability, leverage and good corporate governance. This literature study aims to summarize, examine and discuss the factors that influence the occurrence of tax evasion in this case focused on banking companies listed on the IDX. This research was conducted using the literature review method in which this study used secondary data. The results of this literature study are expected to be a reference for further researchers to be able to develop research on tax avoidance.